Excavating the remains of the left: radical geography and political affirmation. Issue 3 (2nd September 2019) - Parameswaran, Ameet
ABSTRACT: This essay focuses on two works that can be seen as broadly aligned to the Left, across two diverging historical and geographical contexts. The first is the iconic film Amma Ariyan (Report to Mother; 1985) directed by John Abraham under the banner of Odessa movies. As a docu-fiction, the film uses actual footage from the political struggles and agitations and restages certain events with the actual participants involved to document and critique the actions, dreams and failures of the Left movement of the preceding decades in the South-Indian state of Kerala. The second is the performance titled, Atlas of Communism directed by the Argentinean director, Lola Arias that premiered in Maxim Gorki theatre in 2016. Using testimonial format, the performance brings together people who stage their first-person narratives to critically look back at the failure of GDR and the contemporary unified Germany. By paying attention to the ways in which rhythms and scales redefine experiences and the everyday life in these works, the essay explores how excavating and critiquing the past as failure becomes a worksite of the Left precisely because this excavation also offers an affirmation as a determinate matter in a given situation.